Traditional Deepana Pachana Recipes with Pathya-Apathya for ‘Agnimandya’ (International Journal of Ayurveda and Pharma Research, 2025)
The advancement of industrialization and communications leads to faulty life style, food habits, food quality, sleep habits, increased level of stress etc. which causes Tridosha Prakopa and vitiated Jatharagni (digestive fire) results in Agnimandya. According to Charak Samhita, weak state of Jatharagni (Agnimandya) is the root cause of all disease. This disturbed function of Agni is treated with the help of Deepana- Pachana Ahara Kalpana as mentioned in Bhavprakasha followed by Pathya and Apathya given in context of Bhaishajya Ratnavali. Deepana-Panchana traditional recipes are a healing treatment that helps to stimulate the Agni, aiming to bring back balance of the digestive system. This article highlighted the Pathya and Apathya for disturbed state of Jatharaagni and mentioned few Deepana-Pachana traditional recipes to stimulates the secretions of digestive tract and produces sensory-specific appetite. Aims and Objectives: To gather and evaluate traditional Deepana-Pachana recipes and Pathya-Apathya for Agnimandya. Materials and Methods: In Ayurvedic classics the concepts of Pathya- Apathya and Ahara Kalpana are available in scattered manner, hence this study was designed to analyse both together. Conclusion: In Agnimandya, Pathya-Apathya and Ahara Kalpana are cornerstones of management. Ahara Kalpana is a healing art that turns food from a possible burden into a powerful remedy.